Growth, feed conversion and retention, and proximate of eel juvenile treated by immersion of recombinant giant grouper growth hormone - Handoyo, Boyun; Alimuddin, .; Utomo, Nur Bambang Priyo (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
This study was aimed to determine the immersion dose of recombinant giant grouper growth hormone (rElGH) to increase growth of eel juvenile (glass eel). After shock salinity treatment (NaCl 3% for 2 min), glass eel were immersed in water containing 0.9% NaCl, 0.01% bovine serum albumin, and different of dose of rElGH (0, 0.12, 1.2, 12 and 120 mg/L). Glass eel were fed on blood worm for the first month, and commercial diet for the second month of rearing. Fish rearing was performed in 60 L glass aquarium at density of 150 fish per aquarium. The results showed that higher in growth body weight was obtained in immersion dose of 12 mg/L, by increment of about 37.4% higher compared to that of control. The immersion dose of 12 mg/L also increased specific growth rate by 29.3% higher (p<0.05) compared to control. Furthermore, at that immersion treatment, feed conversion ratio of blood worm and commercial diet decreased by 33.7% and 25.6% compared to control, respectively. Protein (7.15±0.08%) and lipid (9.95±0.10%) retentions in 12 mg/L rElGH-treated fish were higher (p<0.05) than those of control (protein 6.17±0.07%; lipid 5.73±0.06%). Lower in protein content (12.73%), while higher content in lipid (8.35%) and crude carbohydrate (3.22%) were found in 12 mg/L rElGH-treated fish compared to those of control (13.24%, 5.90%, and 1.76%, respectively). Thus, in general, rElGH immersion dose of 12 mg/L could generate high performances of eel juvenile, and application of rElGH can be useful to increase aquaculture eel production.Keywords: immersion dose, growth hormone, growth, glass eel